1997
DOI: 10.1177/00220345970760110901
|View full text |Cite
|
Sign up to set email alerts
|

A Three-year Clinical Trial of a Combination of Trimetaphosphate and Sodium Fluoride in Silica Toothpastes

Abstract: The relative efficacy of NaF silica toothpastes containing 1000 ppm fluoride and 1500 ppm fluoride in the control of dental caries is not clear-cut. Also, it has not been established that incorporation of trimetaphosphate (TMP) improves the anticaries activity of NaF toothpastes. A three-year clinical trial was conducted to test the hypotheses that: (i) the anticaries activity of NaF toothpastes containing 1500 ppm F was greater than that of NaF toothpastes containing 1000 ppm F, and (ii) inclusion of TMP impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
7

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 7 publications
4
56
1
7
Order By: Relevance
“…Some clinical studies have shown that with 1000 to 2500 ppm F toothpaste an increase of 6% is obtained in dental caries protection for each 500 ppm (23,35).…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical studies have shown that with 1000 to 2500 ppm F toothpaste an increase of 6% is obtained in dental caries protection for each 500 ppm (23,35).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials indicate that within the range 1,000 to 2,500 ppm F an increase in fluoride of around 500 ppm results in an additional 6% reduction in dental caries. 17,18 In the UK 41% of the parents of young children aged 1fi to 2fi years claim to use a toothpaste containing less than 600 ppm F. 10 Toothpastes containing higher concentrations of fluoride confer greater protection against dental caries but increase the risk of fluorosis. In contrast, low fluoride toothpastes provide less protection against dental caries but reduce the risk of fluorosis.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were subjects wearing fixed orthodontic appliances and subjects unable to be exposed to radiographs for medical/specific reasons. Considering that caries prevalence in young adults in Italy is generally high, 14 a power analysis was performed to calculate an adequate sample size to compare the different caries detection methods. The number was fixed at 48 subjects.…”
Section: Sample and Detection Methodsmentioning
confidence: 99%